Federal Supreme Court Judgements Supplementing The Constitution (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Federal Supreme Court stands at the head of the hierarchy of the judicial organization in Iraq, as it is the highest court in terms of status and the heaviest in terms of tasks and specializations. It is unavoidable for any party to abide by its provisions, or else it will be considered as violating the constitution. Although the court is, in the end, an authority established under the constitution, a study of the decisions it issued proves that it has sometimes stripped itself of the mantle of the original founding authority that lays down the constitution and imposes its provisions. From a deficiency or similar to a defect, and those decisions would have added to the aforementioned texts provisions that the Constitution had not previously mentioned, and some of their decisions would paralyze provisions in the constitution and hold them out of force, while others would have added to the court a margin of jurisdiction that it does not have according to the explicit provisions of the constitution. The research is an attempt to shed light on these decisions and to reveal what has been secretly leaked from provisions complementary to the constitution, among their multiplication and vocabulary.